(untitled) (Revista de Estudios Europeos, 2026)
The European Union counts with a complex financial system composed by a series of own resources that are able to develop their competences and achieve the goals that are established in the treaties. However, the COVID-19 pandemic had serious economic consequences for the Union and with the aim to guarantee an early recovery they resort to loans that fund the Recovery Mechanism. To approach this debt and the new challenges that the UE faces, like the russian threat, is necessary the reform of the financial system. Therefore, in this article, an study of the actual components of those financial systems and the reforms that the European Comision has set up in the last years is going to be realized, analyzing the new resources that plans to implement.